The Combined Action of Duplicated Boron Transporters Is Required for Maize Growth in Boron-Deficient Conditions. Issue 4 (1st August 2017) - Chatterjee, Mithu; Liu, Qiujie; Menello, Caitlin; Galli, Mary; Gallavotti, Andrea
Abstract: The micronutrient boron is essential in maintaining the structure of plant cell walls and is critical for high yields in crop species. Boron can move into plants by diffusion or by active and facilitated transport mechanisms. We recently showed that mutations in the maize boron efflux transporter ROTTEN EAR (RTE) cause severe developmental defects and sterility. RTE is part of a small gene family containing five additional members ( RTE2 – RTE6 ) that show tissue-specific expression. The close paralogous gene RTE2 encodes a protein with 95% amino acid identity with RTE and is similarly expressed in shoot and root cells surrounding the vasculature. Despite sharing a similar function with RTE, mutations in the RTE2 gene do not cause growth defects in the shoot, even in boron-deficient conditions. However, rte2 mutants strongly enhance the rte phenotype in soils with low boron content, producing shorter plants that fail to form all reproductive structures. The joint action of RTE and RTE2 is also required in root development. These defects can be fully complemented by supplying boric acid, suggesting that diffusion or additional transport mechanisms overcome active boron transport deficiencies in the presence of an excess of boron. Overall, these results suggest that RTE2 and RTE function are essential for maize shoot and root growth in boron-deficient conditions.